The Relationship between Body Mass Index, Body Fat Percentage, and Dietary Intake with Muscle Fatigue in Adolescent Football Players - Mochammad Rizal, - (Center for Academic Publications Japan, 2020)
It is important for football players to maintain muscle strength through the entire match. The aim of this study was to investigate body mass index (BMI), body fat percentage (BF%), dietary intake (energy, carbohydrate, and protein) and its relationship with muscle fatigue among adolescent football players. This was a cross-sectional study involving 26 football players aged 15–17 y. BMI was determined using WHO Anhtro Plus, BF% was analyzed using Bioelectrical Impedance Analysis (BIA) and categorized using bodyfat curves for children, and dietary intake was assessed using 3×24 h dietary recall. Running-Based Anaerobic Sprint Test (RAST) was conducted twice and averaged to identify muscle fatigue. Pearson correlation and multiple-regression analysis were performed to determine the relationship between variables. The results showed that overall participants had healthy weight (17.61±1.82 kg/m2), good diet pattern (energy 99.08±14.34%, carbohydrate 92.88±9.54% and protein 95.96±23.41%), but low body fat (6.76±2.12%). In pearson test, negative correlations were found in muscle fatigue and BMI (r=−0.393, p=0.047), as well as BF% (r=−0.458, p=0.019), but positive between muscle fatigue and energy intake (r=0.538, p=0.005). Furthermore, multiple-regression analysis only confirmed statistically significant relationship between energy intake and muscle fatigue (p=0.028). We conclude that the higher BMI and BF% may lead to greater muscle fatigue, while higher energy intake has significant improvement to reduce muscle fatigue. Hence, it is essential for football players to consume adequate energy, and consider to maintain BMI and BF% at optimal range.